2011
DOI: 10.1007/s00296-011-1856-4
|View full text |Cite
|
Sign up to set email alerts
|

Visceral muscle dysmotility syndrome in systemic lupus erythematosus: case report and review of the literature

Abstract: Intestinal pseudo-obstruction (IPO) is not uncommon in systemic lupus erythematosus (SLE), and IPO in SLE has an apparent association with ureterohydronephrosis. However, hepatobiliary dilatation without mechanical obstruction presenting together with IPO and ureterohydronephrosis is much more scarce in SLE. Here, we named this rare triad of IPO, ureterohydronephrosis, and biliary tract dilatation as visceral muscle dysmotility syndrome (VMDS). It always imitates an acute abdomen and is even life-threatening i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 8 publications
0
17
0
Order By: Relevance
“…Corticosteroids (methylprednisolone and prednisone) were used as the initial and first-line immunosuppressive therapy in 27 patients (68%), 4 9 , 11 , 12 , 14 , 15 , 17 21 , 22 25 18 of them were given pulses of high dose corticosteroids (500 mg or 1000 mg/day), 5 , 6 , 9 , 11 14 , 18 21 , 22 , 23 , 25 and 9 patients were discharged on 1 to 2 mg/kg/day methylprednisolone or prednisolone. 4 , 7 , 8 , 15 , 17 , 21 , 24 Twenty-two (81%) of them had a good response to corticosteroids.…”
Section: Resultsmentioning
confidence: 99%
“…Corticosteroids (methylprednisolone and prednisone) were used as the initial and first-line immunosuppressive therapy in 27 patients (68%), 4 9 , 11 , 12 , 14 , 15 , 17 21 , 22 25 18 of them were given pulses of high dose corticosteroids (500 mg or 1000 mg/day), 5 , 6 , 9 , 11 14 , 18 21 , 22 , 23 , 25 and 9 patients were discharged on 1 to 2 mg/kg/day methylprednisolone or prednisolone. 4 , 7 , 8 , 15 , 17 , 21 , 24 Twenty-two (81%) of them had a good response to corticosteroids.…”
Section: Resultsmentioning
confidence: 99%
“… 1 In addition, Chen et al observed the presence of a distended common bile duct without any evidence of mechanical obstruction with IPO in patients with SLE. 16 However, no histopathologic evidence of vasculitis was found in some cases of IPO in SLE. 1 17 18 Another pathophysiological mechanism of IPO is an intrinsic muscle dysmotility.…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenic mechanisms have not been clarified, high-dose steroids are helpful in improving the symptoms of IPO in SLE. 2 7 16 Intravenous methylprednisolone initiated at 1 mg/kg/day for 3 days, followed by oral prednisone 1 mg/kg/day resulted in a good clinical response in most cases. 2 8 In this case, the therapeutic effect of oral prednisone could not be evaluated due to poor compliance induced by side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pathophysiological mechanisms underlying the development of IPO in SLE have not been clearly elucidated, although proposed mechanisms include development of visceral smooth muscle injury and dysmotility subsequent to immune-complex mediated vasculitis. The smooth muscle dysfunction may be diffuse and may involve urinary and biliary systems as well [8][9][10]. Mesenteric ischemia due to LMV may be associated with a number of findings in abdominal CT including focal or diffuse intestinal wall thickening, enlarged intestinal segments, abnormal contrast enhancement in the intestines (target or double halo sign), mesenteric edema, engorgement of the vascular structures penetrating the intestinal wall, and ascites.…”
Section: Discussionmentioning
confidence: 99%